Fermentation of jack bean milk using three selected lactic acid bacteria and their antioxidant properties - Utami, Tyas; Sari, Ika Purnama; Cahyanto, Muhammad Nur (Indonesian Food and Nutrition Progress, 2025)
Three strains of lactic acid bacteria (LAB), Lactobacillus plantarum WGK 4, Streptococcus thermophilus Dad 11, and Lactobacillus plantarum Dad 13, were used for fermentation of jack bean milk and studied their capability to increase the antioxidant activity. Fermentations were carried out at 37oC for 24 h for each strain. Cell growth, titratable acidity (TA), pH, β-glucosidase activity, and total phenolic content were monitored every six hours. Quantification of isoflavones was determined using UFLC (Ultra Fast Liquid Chromatography). The antioxidant properties were investigated using the 1,1-diphenyl-2-picrylhydrazyl (DPPH) method. The result showed that all three LAB strains grew well in jack bean milk to 9.15- 9.26 log CFU/ml, produced acid and decreased the pH to 4.71-5.00 after 24 h fermentation. During fermentation, all three LAB strains could produce β-glucosidase (27.08-27.18 mU/ml) and released aglycones content in jack bean milk (3.71- 4.02 µg/g daidzein and 9.00-10.26 µg/g genistein). The phenolic content and DPPH radical scavenging activity increased 1.1-1.4 fold and 1.4 fold (30-42%), respectively. The results indicate all three LAB strains have a similar ability to increase antioxidant properties and potentially be good starter cultures for fermentation in jack bean milk.